Pengaruh Pengalaman Auditor dan Independensi Pada Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderasi - Sarca, Delsi Nia; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
The purpose of this study was to determine the effect of auditor experience and independence on audit quality with auditor ethics as a moderating variable. This research was conducted on all KAPs that are still operating in Bali Province. The sampling technique used was purposive sampling. Data were analyzed using the Moderated Regression Analysis (MRA) test. The results of the analysis show that the auditor's experience has a positive effect on audit quality, auditor independence has a positive effect on audit quality, auditor ethics strengthens the influence of auditor experience on audit quality and auditor ethics reinforces the influence of independence on audit quality in KAP Bali Province. Keywords: Auditor experience, independence, auditor ethics, audit quality